2020
DOI: 10.1186/s12866-020-01773-z
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of koumiss microbiota and organic acids and their effects on koumiss taste

Abstract: Background: Koumiss is a naturally fermented mare's milk. Over recent decades, numerous studies have revealed the diversity of lactic acid bacteria in koumiss. However, there is limited information available regarding its secondary major component yeast profile.Results: A total of 119 bacterial and 36 yeast species were identified among the 14 koumiss samples. The dominant bacterial species in koumiss were Lactobacillus helveticus, Lactobacillus kefiranofaciens, Lactococcus lactis, Lactococcus raffinolactis, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 59 publications
(60 reference statements)
0
15
0
Order By: Relevance
“…The microbiota of kefir and kefir grains comprises species of bacteria ( Lactobacillus, Lactococcus, Streptococcus, Leuconostoc, Acetobacter , and Enterococcus ) and yeasts ( Saccharomyces, Candida, Kluyveromyces, Zygosaccharomyces, Debaryomyces, Issatchenkia, Pichia , and Torulopsis ) (Guzel‐Seydim et al., 2011; Singh & Shah, 2017; Tang et al., 2020). It should be noted that the Codex Alimentarius Commission (CODEX STAN 243–2003) specifically mentions the presence of Lentilactobacillus kefiri (formerly Lb.…”
Section: Inherent Characteristics Of Dairy Products With Potential Immentioning
confidence: 99%
“…The microbiota of kefir and kefir grains comprises species of bacteria ( Lactobacillus, Lactococcus, Streptococcus, Leuconostoc, Acetobacter , and Enterococcus ) and yeasts ( Saccharomyces, Candida, Kluyveromyces, Zygosaccharomyces, Debaryomyces, Issatchenkia, Pichia , and Torulopsis ) (Guzel‐Seydim et al., 2011; Singh & Shah, 2017; Tang et al., 2020). It should be noted that the Codex Alimentarius Commission (CODEX STAN 243–2003) specifically mentions the presence of Lentilactobacillus kefiri (formerly Lb.…”
Section: Inherent Characteristics Of Dairy Products With Potential Immentioning
confidence: 99%
“…The consumption of artisanal koumiss has been reported to alleviate pneumonia, typhus, bronchitis, hypercholesterolemia, and hypertension (Menghe et al, 2004;Rong et al, 2015). Previous studies have reported associations between koumiss fermentative microbes and metabolites with the unique flavor properties and potential therapeutic components (Menghe et al, 2004;Tang et al, 2020). The microbes responsible for koumiss fermentation were mainly lactic acid bacteria (LAB).…”
Section: Introductionmentioning
confidence: 99%
“…The microbes responsible for koumiss fermentation were mainly lactic acid bacteria (LAB). Some LAB not only serve as probiotics but also offer useful industrial features like acting as a biopreservative (Gesudu et al, 2016;Tang et al, 2020). The rich nutrition, potential therapeutic properties, and high microbial diversity of koumiss make it an interesting product to study.…”
Section: Introductionmentioning
confidence: 99%
“…We identified 48 out of 193 strains through a flux-based approach to be ideal candidates limiting the growth of V. harveyi in specific nutrient environments. It is important to note that many strains out of these 48, like B. subtilis, L. casei, L. rhamnosus, L. paracasei, L. sakei, L. sp Koumiss, and L. buchneri, have already reported to be probiotic species (Lim et al, 2014;Hill et al, 2018;Westerik et al, 2018;Rhayat et al, 2019;Xu et al, 2019;Garcıá-Medel et al, 2020;Liao et al, 2020;Tang et al, 2020). Flux variability analysis revealed the production of SCFA, mainly acetate, by a majority of the strains in paired models, signifying the role of this natural byproduct towards growth inhibition of the pathogen.…”
Section: Discussionmentioning
confidence: 99%